2017
DOI: 10.31018/jans.v9i4.1553
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of frontline demonstrations on green gram: Experience from rainfed condition of Rajasthan

Abstract: Pulses being rich in quality protein, minerals and vitamins are inseparable ingredients of diet of majority of Indian population. Despite high nutritive value of pulses and their role in sustainable agriculture desired growth rate in production could not be witnessed. The domestic production of pulses is consistently below the targets and actual domestic requirements are also higher, due to this pulses are being imported. The Krishi Vigyan Kendra Pali has carried out frontline demonstrations on greengram cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The increased grain yield with improved technologies was mainly due to line sowing, seed treatment with biocontrol agents and biofertilizer, use of foliar nutrients, proper irrigation scheduling, use of the optimum dose of NPK, and timely weed management. Other authors have also found similar results of higher seed yields in demonstration plots than of the existing practices in different crops [34][35][36][37][38][39].…”
Section: Seed Yieldsupporting
confidence: 62%
“…The increased grain yield with improved technologies was mainly due to line sowing, seed treatment with biocontrol agents and biofertilizer, use of foliar nutrients, proper irrigation scheduling, use of the optimum dose of NPK, and timely weed management. Other authors have also found similar results of higher seed yields in demonstration plots than of the existing practices in different crops [34][35][36][37][38][39].…”
Section: Seed Yieldsupporting
confidence: 62%